Subinhibitory Concentrations of Amoxicillin, Lincomycin, and Oxytetracycline Commonly Used to Treat Swine Increase Streptococcus suis Biofilm Formation - Waack, Ursula; Nicholson, Tracy L. (Frontiers in Microbiology, 2018)
Streptococcus suis is a bacterial swine pathogen with a significant economic burden. It typically colonizes the tonsil and nasal cavity of swine causing a variety of symptoms ranging from asymptomatic carriage to lethal systemic disease. A key barrier towards the development of improved vaccines or interventions for S. suis infections is a gap in our understanding of the mechanisms contributing to persistence in the host, in which colonized pigs continue to shed and transmit S. suis. We hypothesized that exposure to sub-MICs of antibiotics commonly used by the swine industry would increase the biofilm capacity of S. suis strains. Using a 96-well plate MIC protocol, we experimentally determined the MIC for each of 12 antibiotics for a virulent strain of S. suis strain that consistently formed biofilms using a standard crystal violet assay. Using this static biofilm assay, we demonstrated that sub-MICs of bacitracin, carbadox, chlortetracycline, enrofloxacin, gentamicin, neomycin, sulfadimethoxine, tiamulin, and tylosin did not increase S. suis biofilms. In contrast, we demonstrated that sub-MICs of amoxicillin, lincomycin, and oxytetracycline increased overall biofilm formation under both static and flow conditions. The biofilm formation of eleven additional clinical isolates were measured using the relevant concentrations of amoxicillin, lincomycin, and oxytetracycline. Eight of the eleven strains increased the biofilm formation with lincomycin, seven with amoxicillin, and three with oxytetracycline. Collectively, our data demonstrate that exposure to sub-MICs of these commonly used antibiotics contributes to increased biofilm formation of S. suis, thereby potentially increasing survival and persistence within the respiratory tract of swine.